Treatment of Chronic Anterior Shoulder Dislocation by Coracoid Osteotomy with or without Bristow–Latarjet Procedure - Yong‐liang Yang; Qing‐hu Li; Qi Zhang; Hong‐lei Jia; Bo‐min Wang; Jin‐lei Dong; Dong‐sheng Zhou; Xiao‐mei Wang; Lian‐xin Li (Orthopaedic Surgery, 2020)
Objective To investigate the clinical efficacy and outcomes of the coracoid osteotomy with or without Bristow–Latarjet procedures in the treatment of chronic anterior shoulder dislocation (CASD). Methods Between January 2013 and January 2019, 20 shoulders of 18 patients who were diagnosed with chronic anterior dislocation and underwent open reduction in our trauma center were retrospectively studied. Open coracoid osteotomy with Bristow–Latarjet procedures were performed on 16 shoulders and open coracoid osteotomy without Bristow–Latarjet procedures were performed on four shoulders. Open coracoid osteotomy with or without Bristow–Latarjet procedures were chosen on the basis of the stability of the shoulder after reduction. Outcomes were assessed preoperatively and postoperatively with the visual analog scale (VAS) for pain, the American Shoulder and Elbow Surgeons (ASES) score, the University of California Los Angeles (UCLA) shoulder rating scale, and the range of motion (ROM) for shoulder activity. Results There were three males and 15 females with an average age of 60.94 ± 2.69 years. The time between dislocation and treatment ranged from 21 to 240 days with an average of 73.3 ± 14.4 days. All patients were available for a mean follow‐up of 15.2 ± 4.3 months. No procedure‐related death or incision‐related superficial or deep tissue infection was identified in all cases. No iatrogenic neurovascular injuries or fractures were found in this study. At the time of 12 months follow‐up, the range of motion and the shoulder functional evaluation (VAS [P < 0.001], ASES [P < 0.001], and UCLA score [P < 0.001]) in patients who underwent Bristow–Latarjet procedures were significantly improved. Subluxation after surgical procedure was found and confirmed in one patient and this patient refused to undergo revision surgery. According to the Samilson and Prieto classification system, 16 shoulders were assessed as grade 0, three shoulders were grade 1, one shoulder was grade 2. Conclusions Coracoid osteotomy with or without Bristow–Latarjet procedure yielded an acceptable clinical result in this study. This method has the advantages of enlarging the exposure of surgical field, assisting reduction of shoulder, and convenient conversion to Bristow–Latarjet procedure. It is an efficient and reliable method for treatment of chronic anterior shoulder dislocation. A 69‐year‐old woman diagnosed with right chronic anterior shoulder dislocation with large Hill–Sachs lesion. The latarjet procedure with remplissage technique was applied for this patient.